CHARACTER BUILDING GEN-Z MELALUI PENDIDIKAN POLITIK DI KECAMATAN INDRALAYA UTARA, OGAN ILIR, SUMATERA SELATAN - Mardianto, Mardianto; Khairunnisya, Tuty; Rafinzar, Rahmat; Khairunnas, Khairunnas (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2024)
Gen-Z is currently the center of attention of political actors ahead of the 2024 elections. This generation has an important role in holding the relay for Indonesia's future leadership. Preparing Gen Z to meet this is of course an issue. The implementation method that will be used in this community service activity is in the form of mentoring activities for Lingua Prima Vocational School students in building intelligent political character by increasing their understanding and knowledge of politics. The activities carried out provide material in the form of lectures containing explanations regarding the importance of having knowledge and understanding of the political system and the important role of the younger generation in politics. Young people who are politically intelligent need to have a strong character base, which is instilled in generation Z through character building. The importance of character building in this generation is to help them face complex moral and ethical challenges in the modern world. With strong character building, generation-Z is expected to become young people who have strong principles, understand the importance of authority in politics, and make positive contributions to society. With strong character and a good understanding of politics, the young generation can become agents of positive change in politics and their society. Of course, students need a broad understanding of knowledge regarding political education and politically intelligent young people.